Evaluando el banco de disertaciones y teses de la asociación brasileña de antropología : un análisis cienciométrico - Vanti, Nadia Aurora Peres (2001)
This report presents research currently underway for the Master’s inBiblioteconomics of the PUC-Campinas/SP, in reference to academic productionin the area of Anthropology at Brazilian universities. Using scienciometricanalysis, an attempt is made to measure and compare the contribution of eachinstitution to anthropological research in the country, as well as to plot theevolution of woman participation in this discipline, point out the geographicalareas more widely studied, discover the most discussed issues and cast somelight on certain social, political and institutional factors that may have had anincidence on increasing or decreasing the choice of certain topics apart fromillustrating the application of different quantitative indicators in an electronicdata bank. That is, research goals and a description of their object, themethodology used, the procedure for empiric material collection and the dataanalysis plan are presented. A bibliographic revision is carried out of existingstudies on the subject inside and outside Brazil for the purpose of giving aoverview of quantitative papers related with Anthropology. Lastly, this paperintends to demonstrate how such research may, to a certain extent, contribute tothe development of this specific topic within the fields of Anthropology andInformation Science